Understanding Pre-Exposure Prophylaxis Adherence in Young Women in Kenya. (1st March 2022) - Haberer, Jessica E.; Mugo, Nelly; Bukusi, Elizabeth Ann; Ngure, Kenneth; Kiptinness, Catherine; Oware, Kevin; Garrison, Lindsey E.; Musinguzi, Nicholas; Pyra, Maria; Valenzuela, Susie; Thomas, Katherine K.; Anderson, Peter L.; et al.
Abstract : Objective: To present detailed analyses of long-term pre-exposure prophylaxis (PrEP) use and associated behaviors and perceptions among young Kenyan women. Design: Prospective, observational cohort. Methods: The Monitoring PrEP among Young Adult women Study involved 18 to 24-year-old women at high HIV risk initiating PrEP in Kisumu and Thika, Kenya. Visits for PrEP counseling and dispensing, HIV testing, and socio-behavioral data collection occurred at Month 1 and quarterly for 2 years. PrEP adherence was measured with pharmacy refill and real-time electronic monitoring, plus tenofovir diphosphate levels in 15% of participants. HIV risk behavior and perception were assessed by self-report in weekly short message service surveys from Months 6–24. Predictors of adherence were assessed with multivariable logistic regression analysis. Results: Three hundred forty-eight women (median age 21, VOICE risk score 7) were followed for 617 person-years. Pharmacy refills steadily declined from 100% (Month 0–1) to 54% (Months 22–24). Average electronically monitored adherence similarly declined from 65% (Month 0–1) to 15% (Months 22–24). Electronically monitored adherence had moderately high concordance with tenofovir diphosphate levels (67%). High average adherence (5+ doses/week) was seen at 385/1898 (20%) participant-visits and associated with low baseline VOICE risk score, >1 current sexual partner, ⩽1-hour travel time to clinic, and the Kisumu site. short message service-reported behavior and risk perception were not associated with adherence. Four women acquired HIV (incidence 0.7/100 person-years). Conclusions: PrEP adherence was modest and declined over time. HIV risk was inconsistently associated with adherence; clinic access and site-level factors were also relevant. Relatively low HIV incidence suggests participants may have achieved protection through multiple strategies. Abstract : Supplemental Digital Content is Available in the Text.